IMPLEMENTATION OF RELIGIOUS GUIDANCE FOR DRUG CONVICTS IN AN EFFORT TO REDUCE THE RISK OF RECIDIVISM AT THE TULUNGAGUNG CLASS IIB CORRECTIONAL INSTITUTION - Muhammad Qaedi Rifqi Nuranda; Umar Anwar; Ali Muhammad; Budi Priyatmono (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the implementation of religious-based rehabilitation programs for drug offenders at the Class IIB Correctional Institution in Tulungagung, with a focus on their potential to reduce recidivism. The research is motivated by the high rate of reoffending among drug convicts in Indonesia, highlighting the need for more effective rehabilitation approaches within correctional facilities. Using a qualitative descriptive method, data were collected through in-depth interviews, observations, and documentation involving inmates and correctional officers. The analysis is based on policy implementation theory by George C. Edwards III and religiosity theory by Rodney Stark and Charles Glock. The findings indicate that religious development programs such as Qur’anic recitation, congregational prayers, religious lectures, and worship activities have been implemented consistently. These activities contribute positively to improving inmates’ behavior, increasing spiritual awareness, and strengthening their motivation to avoid reoffending. However, the implementation of the program is constrained by limited human resources, inadequate facilities, and budget restrictions. Despite these challenges, the study finds that religious-based rehabilitation has strong potential as an approach to reducing recidivism. In conclusion, religious development plays a significant role in fostering positive behavioral change among inmates. To maximize its effectiveness, stronger policy support, improved resources, and enhanced collaboration between institutions are necessary to ensure sustainable and impactful rehabilitation outcomes. Keywords: Correctional Facility; Drug Inmates; Policy Implementation; Recidivism; Religious Development